In vivo measurement of the surface energy of human fingernail plates - Zara, Sheikh,; Murdan, Sudaxshina; Poojary, Chitranjan; Patel, Dilan R; Fernandes, João; Angarju (© 2012 International Journal of Cosmetic Science, 2016)
This article was published in the International Journal of Cosmetic Science [© 2012 International Journal of Cosmetic Science] and the definite version is available at: http://discovery.ucl.ac.uk/1366902/1/nail_surface_energy_for_SOPwebsite.pdf